Factors affecting prices of calves and yearlings in Kansas - Lambert, C.; Corah, L.; Grunewald, O. (Kansas State University. Agricultural Experiment Station, 2010)
Data were collected on 85,195 cattle sold in 15 Kansas auctions during October and November 1981. Buyers discounted sick cattle heavily, 'and discounts were heavier on sick calves than yearlings. The discount for bulls vs. steers increased as weight increased, but the discount for heifers vs. steers decreased with increasing weight. Buyers pay little if any premium for thin cattle, but severely discount very thin or fat cattle. Cattle with average fill sold as well or better than shrunk cattle. Gaunt or tanked cattle were heavily discounted. Best prices were paid for lots of 20 to 40 head, with heavy discounts for lots less than 5. Since the price advantage to uniform lots was small, sorting should be kept to a minimum. Large framed, thick muscled cattle sold best, and smaller framed cattle were discounted more in western than eastern Kansas.
Keywords: Beef; Calves; Yearlings